IRANIAN-EGYPTIAN RELATIONS AND THE VISIT OF M. AHMADINEJAD TO CAIRO IN 2013 - A. Baranov (Гуманитарные и юридические исследования)
The article analyzes the consequences of the fall of Hosni Mubarak's pro-American regime in February 2011 in Egypt, due to the events of the Arab Spring, which threatened the entire security system in the Middle East. The coming to power in 2012 of Islamist Mohammed Mursi opened the way for the restoration of diplomatic relations between Egypt and Iran. The union between the two countries could become the basis for a new alignment of forces in the region. The article focuses on the visit of Iranian President Mahmoud Ahmadinejad to Cairo in February 2013. It was the first official visit of this level since the victory of the Islamic Revolution in Iran and the severance of diplomatic relations. The article analyzes the reasons, plans and goals of the visit for official Tehran. The study features the content of the main meetings and bilateral negotiations, both at the official and non-official levels. It is shown that the visit of the Iranian delegation to Cairo demonstrated the presence of objective reasons, both internal and external, which made it impossible to complete the process of restoring full-fledged relations between Iran and Egypt at that time. The military coup and the overthrow of M. Mursi, again "froze" the relations between the two countries for an indeinite time.